Association of Childhood Neighborhood Opportunity With Retinopathy of Prematurity - Altamirano, Francisco; Hoyek, Sandra; Carlson, Kristy; Patel, Nimesh A.; VanderVeen, Deborah K.; Gonzalez, Efren; Oatts, Julius T.; Slopen, Natalie; Oke, Isdin (American journal of ophthalmology, 2025)
Although individual-level factors have been associated with the development of retinopathy of prematurity (ROP), the relationship between neighborhood conditions and ROP has not been well characterized. This study examines the relationship between ROP and a novel indicator of neighborhood conditions, the Child Opportunity Index (COI). Cross-sectional study. Infants who underwent screening for ROP between 2012 and 2021 at 3 neonatal intensive care units. Residential census tracts were used to determine the overall and domain-specific COI scores for each child, linked by year of birth. The primary analysis used the overall COI score, while secondary analyses focused on specific COI subdomains: education, health and environment, and socioeconomic domain. Multivariable logistic regression models were used to estimate the association of COI scores and ROP, adjusting for patient demographics. Children with missing or foreign addresses were excluded, as this precluded COI score assignment. The outcomes included prevalence of ROP and treatment-warranted ROP (TW-ROP). This study included 2468 infants screened for ROP. Infants in the very low opportunity group had lower birth weight (1026 ± 337 grams vs. 1130 ± 320 grams, P < .001) and gestational age (27.8 ± 2.9 weeks vs. 28.5 ± 2.5 weeks, P < .001) compared to infants in the very high opportunity group. In the primary analysis, a 20-point decrease in overall COI score was associated with the diagnosis of ROP (OR = 1.10; 95% CI 1.04-1.16) and TW-ROP (OR = 1.16; 95% CI 1.05-1.30). These associations were no longer significant after adjusting for birthweight and gestational age. In the secondary analysis, a 20-point decrease in the health and environment score was associated with TW-ROP after adjusting for all covariates. Infants from households residing in low opportunity neighborhoods were more likely to develop ROP and TW-ROP. The relationship between ROP and COI appears to be largely driven by increased prematurity in low opportunity neighborhoods. Composite indices such as the COI may help identify children at increased risk for vision-threatening conditions and enable targeted interventions.